Correlation between birth weight, age and weight at beginning of rumination in Zebus - Bacalhau, Augrizônio dos santos; Albuquerque, Rômulo Pontes de Freitas; Marinho, Janduy Silva; dos Santos, Elson Soares (Pesquisa Agropecuaria Brasileira, 1992)
Correlations between birth weight, age and weight at beginning of rumination were studied in 75 Gyr and 72 Guzerat calves that were born in 1985 and 1986, reared in a semi-intensive regime. Data were analysed by breed, using, the least squares methodology. The matematical model included the effects of sex, year and season of birth. The average of birth weight, age and weight at the beginning rumination were 31.76 + 0.51 kg, 27.67 + 1.10 days and 44.55 ± 0.79 kg for Guzerat breed, respectively. For the Gyr, the data were 24.68 ± 0.32 kg, 25.69 ± 0.57 days and 39.28 ± 0.82 kg, respectively. The analysis of variance showed significant effects (P < 0.05) of year of birth on the birth weight of Gyr and Guzerat calves, and of sex of calf in that last breed. The results showed a significant positive correlation between birth weight and weight at the beginning of rumination. However, it was shown that there is no significant correlation between birth weight and age. at the beginning of rumination, indicating that the age at the beginning of rumination of zebu salves is influenced by other factors than birth weight.